1966
DOI: 10.1149/1.2423782
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon Fuel Cells with Fluoride Electrolytes

Abstract: Fuel cell investigations using saturated hydrocarbon fuels with aqueous cesium salt electrolytes and Teflon bonded platinum electrodes have shown that the acidic system normalCsF‐HF‐H2O comprises a suitable set of electrolytes for high performance hydrocarbon fuel cells. The effects of electrolyte composition and temperature on cell performance were studied with emphasis on propane as the fuel. Cell performance was also determined as a function of the molecular structure of the fuel using the homologous seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

1967
1967
2005
2005

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 10 publications
2
34
0
Order By: Relevance
“…An investigation of various fuels [6], concluded that the largest oxidation rates were obtained with propane. In sufficiently concentrated electrolytes, the small water content may cause the rate of water diffusion to be rate-limiting [3].…”
Section: Several Other Factors Influence the Performance Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…An investigation of various fuels [6], concluded that the largest oxidation rates were obtained with propane. In sufficiently concentrated electrolytes, the small water content may cause the rate of water diffusion to be rate-limiting [3].…”
Section: Several Other Factors Influence the Performance Ofmentioning
confidence: 99%
“…The increase in operating temperature that is possible with H 3 PO 4 fuel cells increases kinetics and current densities. A binary CsF-HF electrolyte that operated at elevated temperatures was also promising but it had water management problems [6]. Therefore, H 3 PO 4 was considered to be the most practical electrolyte [1] and was chosen as the electrolyte for this study.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship for the fraction of the surface covered by hydrocarbon species (and therefore not available to hydrogen) is expressed by O.Oo.3QsH --O.Oo.3Q H 0.00.3eric = [5] 0-00.3QsH…”
Section: ] To Calculate the Values Of The Bracketed Expression Desimentioning
confidence: 99%
“…For these reasons and because of the fact that fuel cells using hydrofluoric acid electrolyte oxidize saturated hydrocarbons at high current densities, it was decided that a study would be made of the adsorption of a saturated hydrocarbon on platinum in hydrofluoric acid. Propane was selected as the simplest typical saturated hydrocarbon because it is the smallest molecule containing both CH2 and CH3 groups, and it exhibits 1Present address: Argonne National Laboratory, Argonne, Illinois 60439. good reactivity on platinum in hydrofluoric acid (5,6).…”
mentioning
confidence: 99%
“…In addition to inventing and developing the PEFC, this group of researchers examined the thermodynamics of fuel cells 22,23 and did a considerable amount of work on direct-hydrocarbon fuel cells, [24][25][26][27][28][29] as well as direct-ammonia fuel cells. 30,31 They also developed new electrode structures 32,33 and examined new electrocatalysts for use with reformate fuels.…”
Section: General Fuel Cell Topicsmentioning
confidence: 99%